Phytochemical properties of Iranian organic saffron stigma: antioxidant, anticancer and apoptotic approaches - Behdani, M. A.; Hoshyar, R. (Cellular and Molecular Biology, 2016)
Agronomic and environmental factors affect quality and quantity of constituents in Saffron.  In this study, we compared chemical and antioxidant compounds of organic (OS) and inorganic (IOS) stigma of saffron and evaluated their anti-proliferative and apoptosis effects on cancer cells. Total antioxidant capacity of both saffron were characterized by FRAP, DPPH and Folin-Ciocalteu. HPLC and MTT methods were used to assay the amount of their secondary metabolites and anticancer effects, respectively. The expression of two apoptosis-related genes in treated cells evaluated by quantitative Real Time-PCR analysis. Our data indicated that OS has more secondary metabolites, antioxidant and cytotoxic properties compared to IOS. OS significantly inhibited cell viability in a dose- and time- dependent manner. Herb-induced apoptosis associated with increased expression of Bax and decreased Bcl2 gene leading eventually to a time-dependent increase in Bax/Bcl-2 ratio. Therefore, we can suggest organic saffron has promising and selective inhibitory effects on cancer cell proliferation.